JUAL BELI GHARAR (Tinjauan terhadap Proses dan Obyek Transaksi Jual Beli) (Mazahib, 2007)
Islam has urged its follower to seek sustenance through trading. As a matter of fact, the Prophet is a role model of a successful trader and so did many of the Prophet’s companion e.g. Abu Bakar, Umar Ibn Khattab, Utsman Ibn Affan, Abdurrahman Ibn Auf and so forth. When urging the trading, Islam has given guidelines of what is allowed and prohibited. One of them is the prohibition of gharar because it involves uncertainty (betting or gambling) in doing business. This article is to discuss the concept of gharar in Islamic business law. Accordingly, there are two types of gharar i.e. uncertainty in contract and uncertainty in object of contract.